Fat mass and obesity-associated protein (FTO) mediates signal transducer and activator of transcription 3 (STAT3)-drived resistance of breast cancer to doxorubicin. Issue 1 (1st January 2021) - Wang, Yan; Cheng, Zhiqiang; Xu, Jing; Lai, Meina; Liu, Liming; Zuo, Min; Dang, Lin
ABSTRACT: Excessive activation of signal transducer and activator of transcription 3 (STAT3) is implicated in breast cancer (BC) chemoresistance, but its underlying mechanism is not fully understood. There are STAT3 binding sites in fat mass and obesity-associated protein (FTO) promoter region, thus STAT3 may regulate the transcription of FTO. This study aimed to investigate the correlation between FTO and STAT3 in BC chemoresistance. Herein, FTO and STAT3 were highly expressed in doxorubicin-resistant BC (BC-DoxR) cells. CHIP assay verified the binding between STAT3 and FTO promoter in BC-DoxR cells. Dual luciferase reporter assay showed that FTO promoter activity was inhibited by S3I-201 (STAT3 inhibitor) but enhanced by epidermal growth factor (EGF, STAT3 activator) in BC-DoxR and BC cells. FTO mRNA and protein expression were suppressed by S3I-201 in BC-DoxR cells and EGF-stimulated BC cells. Notably, FTO regulated total N6-methyladenosine (m6A) levels in BC-DoxR and BC cells but could not affect STAT3 mRNA expression, indicating that FTO was not involved in the m6A modification of STAT3. However, FTO could activate STAT3 signaling in BC-DoxR and BC cells. Besides, FTO knockdown inhibited the doxorubicin resistance of BC-DoxR cells, while FTO overexpression enhanced the doxorubicin resistance and weakened the doxorubicin sensitivity of BC cells. Moreover, decreased doxorubicin resistance by STAT3 knockdown was abolished by FTO overexpression and decreased doxorubicin sensitivity by STAT3 overexpression was reversed by FTO knockdown, indicating that FTO was implicated in STAT3-mediated doxorubicin resistance and impairment of doxorubicin sensitivity of BC cells. Altogether, our findings provide a mechanism underlying BC doxorubicin resistance. Graphical abstract: uf0001